FUNCTIONALIZATION OF 3D FIBROUS SCAFFOLDS PREPARED USING CENTRIFUGAL SPINNING WITH LIPOSOMES AS A SIMPLE DRUG DELIVERY SYSTEM - Michala Rampichová; Matej Buzgo; Věra Lukášová; Andrea Míčková; Karolína Vocetková; Věra Sovková; Franco Rustichelli; Evžen Amler (Acta Polytechnica CTU Proceedings)
3D materials supporting cell adhesion, infiltration and proliferation are crucial for bone tissue engineering. In the current study we combined PCL fibers prepared using centrifugal spinning with adhered liposomes filled with platelet lysate as a natural source of growth factors. The scaffold was seeded with MG-63 cells and tested in vitro as a potential drug delivery system for bone tissue engineering.